A critical realist perspective on humanness as a meaningful re‐entry of relational distinctions. (15th October 2020) - Donati, Pierpaolo
Abstract: All forms of humanism that consider the human as a yardstick of society are marginalized by a Digital Technological Matrix that dominates the human, minimizes its role, and transforms it, to the point of dissolving its boundaries with the non‐human. Speaking of essence and human dignity still make sense? The thesis of this contribution is that the human is redefined and re‐evaluated precisely due to the process that makes the human 'eccentric' and places it in the system environment. The human re‐emerges as an intransitive essence endowed with an original, humble, relational dignity . The human can and must be regenerated through the relational reflexivity operated by relational subjects contextually capable of re‐entering within themselves the constitutive distinctions of their humanness, both individual and collective. The specific 'intransitive' essence of the human lies in the impossibility for it to renounce the meaning of its own existence. Precisely because of the confrontation with robotic technologies, the value of the human being and his dignity change.